Ritual Hitching Posts Serge Among the Buryats in the 21st Century - Sesegma G. Zhambalova (Гуманитарный вектор)
The article deals with a little-studied topic with the aim of studying localization of Buryat ritual hitching posts serge in the space from Ust-Orda district to Cape Khoboy on Olkhon Island in the 21st century. The article is based on the field observations and materials, literary and electronic sources. The hypothesis of the study was proved – in conditions of globalization and active increase in international tourist flows, the Buryats are expanding the boundaries of their own sacred world to create a specific system of protective mechanisms against intensive foreign cultural influence. Sacred objects contribute to the preservation of the fragile ecology of the region. One of the key methods used in the article is ideographic method, which is supplemented with analysis and generalization. There are three entrance signs/complexes, in which the central place is given to ritual hitching posts on the section of the R-418 highway from Irkutsk to the border of the Olkhonsky district. On this section of the road there is a barisa, a ritual complex, with three serge. In the Olkhon region, nine serge are located at the mouth of the river Angi near Mount Yordo where the Yordyn Games are held. On the island of Olkhon near the cape Burkhan, 13 ritual hitching posts have been erected in honor of the “13 northern noyons”, occupying a special place in the shamanic pantheon of Buryats. There is a ritual hitching post serge on Cape Khoboy. The researched cult objects were established in the 21st century by the decision of the population and are all-Olkhon, and possibly all Buryat. The innovative character of the ritual hitching posts lies in their considerable size and in their installation in places where they were not previously installed, thus expanding the sacred territory. These considered Olkhon serge, despite of their increased size, retain their authenticity, in contrast to the stylized serge standing on the entrance steles. A new organization of the socio-cultural space with the help of ritual hitching posts indicates that the ethnic culture has been transforming into a national one.